Persepsi Guru atas Supervisi Kepemimpinan Kepala Madrasah terhadap Kinerja Guru - Yunita Endra Megiati; Noor Komari Pratiwi (Universitas Indraprasta PGRI Jakarta, 2021)
The purpose of this study is to discover teachers’ perception of the leadership supervision of madrasah principals on teachers performance. The research method used was a survey with a sample of all teachers at MI Al Hikmah Bekasi, totaling twenty people. This study was conducted in 2020. Data on teacher perceptions towards the supervision from the head of madrasah on teacher performance were obtained through a questionnaire compiled by the researcher. The hypothesis of this study was that teachers' perceptions towards the supervision of madrasah principals have a significant effect on teachers performance. The statistical test results showed the prob value. F(sig.) <0.05, which meant that the teacher's perception of the leadership supervision of the head of madrasah (X) had a significant effect on teacher performance (Y). The value of the multiple correlation coefficient (R) was 0.862, indicating a very strong relationship between the variable teacher perceptions of the supervision of the head of madrasah (X) and the teacher performance variable (Y). Furthermore, the coefficient of determination (R2) 0.743, indicating that the variable teacher perceptions of the supervision of the head of madrasah (X) had an effect of 74.3% on teacher performance (Y), while 25.7% was influenced by other variables. The conclusion is that teachers' perceptions of the leadership supervision of madrasah principals have a significant effect on teacher performance.